The Perception of Corruption among Experts, Well-Informed Citizens and Ordinary People - Pocienė, Aušra (Kriminologijos studijos, 2018)
[full article and abstract in Lithuanian; abstract in English]This article presents an analysis based on Alfred Schutz’s epistemological stratification; it asks how do three epistemic groups perceive the phenomenon of corruption in Lithuania, these three groups being: (1) “experts,” scientists and criminal justice representatives working with corruption cases; (2) “well informed citizens,” politicians and the representatives of mass media, and (3) “people from the street,” ordinary Lithuanian citizens. The analysis is based on the data of focus groups discussions that were performed in the framework of the project “Social Context of Corruption: An Analysis of Macro, Meso and Micro Level Factors” that was implemented at Vilnius University, Faculty of Philosophy during 2015–2017.The group discourses are analyzed from perspectives of three levels: (1) corruption as a worldwide phenomenon on a macro level; (2) the extent and forms of corruption on the social-meso level, and (3) the origin of corruption and the concept of the “corrupted man” on the micro-individual level. In the article, it is also analyzed how experts, “well informed citizens” and ordinary people assess the current means of corruption control and prevention in Lithuania and what other suggestions of prevention they have.The analysis showed that the main focus of three groups is localized on the meso level, discussing the extent and level of corruption in society, its main forms and corrupted groups. Only little attention is paid to the micro-individual level, where corruption takes it roots as a moral problem. Also, the predominant concept of corruption among ordinary people is almost the same as embedded in criminal law – as a crime committed by white collar individuals who have a particular amount of power at their disposal. Such a narrow legal perception of corruption becomes dysfunctional for effective crime control and prevention as far as it overlooks the widespread culture of corruption that penetrates all social layers, not only the white collars.The main criticism of current corruption control and prevention policy is based on its demonstrative ineffective and dysfunctional character, while the main perspective of corruption prevention is seen in general social education and primary socialization. The experts and ordinary citizens view the culture of corruption as possibly being diminished only by strengthening social relations and restoring community commitment.
Keywords: perception of corruption; control and prevention of corruption; epistemic groups